Trope of Containment: Shale Oil, Risk Rhetoric, and the Lac-Mégantic Disaster - Angelich, Christian (My University, 2019)
My fieldwork was located in Lac-Mégantic, Québec, where a train carrying Bakken shale oil derailed on July 6, 2013 causing a pool fire that killed 47 people. The evacuation of 2,000 residents was a catalyst for public discourse on hazmat-by-rail in North America. This study combines participant observation and oral history with a critical examination of rhetoric used in response to shale oil transportation, neoliberal capitalism, environmental justice, and discourses on sustainability. There have been 26 hazmat derailments since 2013, which occurred despite regulatory fixes, and demonstrate what I call a trope of containment. When rail accidents happen, public safety knowledge is strategically contained to myopic risk frames that benefit industry. My hope is that survivor stories can offer oppositional narratives to the transportation of hydrocarbons along a rail network that sustains itself through regulatory capture. This project also examines relationships between fracking, climate change, and violence created by the production of fossil fuels. My goal is to demonstrate the failures that occur when containment strategies are institutionalized as a safety-based ideology. Secondly, critical pedagogical opportunities exist through an unmasking of rhetoric used to sustain a carbon economy, which works to delay alternative energy solutions to global warming. Included are research opportunities that can fill policy voids left by states with limited funds linking public safety to community education.
University of Minnesota Ph.D. dissertation. August 2019. Major: Communication Studies. Advisor: Mark Pedelty. 1 computer file (PDF); vi, 239 pages.
Keywords: climate change; hazmat; oil-by-rail; public safety; rhetoric; shale oil